Psychiatric profiles of mothers who take Ecstasy/MDMA during pregnancy: Reduced depression 1 year after giving birth and quitting Ecstasy. (January 2014) - Turner, John JD; Parrott, Andrew C; Goodwin, Julia; Moore, Derek G; Fulton, Sarah; Min, Meeyoung O; Singer, Lynn T
Background: The recreational drug MDMA (3, 4-methylenedioxymethamphetamine) or 'Ecstasy' is associated with heightened psychiatric distress and feelings of depression. The Drugs and Infancy Study (DAISY) monitored the psychiatric symptom profiles of mothers who used Ecstasy/MDMA while pregnant, and followed them over the first year post-partum. Methods: We compared 28 young women whom took MDMA during their pregnancy with a polydrug control group of 68 women who took other psychoactive drugs while pregnant. The Brief Symptom Inventory (BSI) was completed for several periods: The first trimester of pregnancy; and 1, 4 and 12 months after childbirth. Recreational drug use was monitored at each time point. Results: During the first trimester of pregnancy, MDMA-using mothers reported higher depression scores than the polydrug controls. At 1 year after childbirth, their BSI depression scores were significantly lower, now closer to the control group values. At the same time point, their self-reported use of MDMA became nearly zero, in contrast to their continued use of Cannabis /marijuana, nicotine and alcohol. We found significant symptom reductions in those with BSI obsessive-compulsive and interpersonal sensitivity, following Ecstasy/MDMA cessation. Conclusions: The findings from this unique prospective study of young recreational drug-using mothers are consistent with previous reports of improved psychiatric health after quitting MDMA.